Politisasi Bahasa Melalui Eufemisme dalam Program Berita di Televisi - Hermaliza; Ermawati. S (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This study discussed the politicization of language through euphemisms that conducted at the time of news broadcasts on television stations by noticing the background of the use of the euphemisms. Euphemism in the mass media is not merely aimed at replacing taboo words, but rather is ideological politics. The problem raised in this study was